Economic growth: the structure of production and monetary policies - Villalobos Céspedes, Daniel (2024)
There is much literature and discussion on the topic of economic growth and money supply given the numerous points of view that exist. In the thick of the COVID-19 pandemic, policymakers and prominent economists looked to revive employment, investment, and production and to tame rising inflation. Monetary and fiscal policies promoted prior to the outbreak of COVID-19 seem to be the core issue. This essay examines Hayek’s critical assumptions on the effects of the money supply on both the volume and direction of output through production structure, prices, and interest rates. We provide a theoretical model to analyze essential macroeconomic variables and to discover new formulas to measure economic trends and forecast the interest rate at any given instant. Analyzing data from the United States of America according to the Bureau of Economic Analysis (BEA) and the Federal Reserve (Fed), the results suggest that one year ago the Fed should have aimed for an interest rate of approximately four percent (4.0%). In the Addendum to this paper, we include a table demonstrating the usefulness of the proposed model when dealing with steady economic growth.